Teacher and Parents Persuasion of use of Picture Exchange Communication System to improve Attention Span for Autistic Students in Abu Dhabi Autism Center - Eyadeh Alzoubi, Ibrahim Hassan; Syed Sahuri, Sarifah Nurhanum; Ismail , Hayati (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
The fact has been established by [20] one out of every 146 newborns in UAE is affected with Autism Spectrum Disorder, and measuring the attention span using what method is difficult. It has been emphasized by [21] Children with ASD have a shorter attention span; hence the purpose of this study is to increase the attention span of autistic children in Abu Dhabi by using Picture Exchange Communication System (PECS). PECS is a picture-based communication method for people with little or no communication abilities to communicate using pictures [23]. PECS is used in the classroom by teaching the children to make their requests by handing them an exchange card representing what they want. The goal of this study is to persuade parents and teachers of the use of PECS to improve the attention span of autistic students at the Abu Dhabi Autism Center. Three samples are used in this study. The children are used as the samples of the study. Three parents and three teachers are interviewed to find out how persuaded they are about the use of PECS in increasing the attention span of the children at the Abu Dhabi center. Nine participants are involved in this study. The location of the study is the Abu Dhabi center. The experimenter will be the observer in this study. This study shows how effective the use of PECS is in improving the attention span of autistic children at the Abu Dhabi Autism Center. As a result, PECS is effective in increasing the attention span of autistic children, and parents and teachers are convinced that using PECS at Abu Dhabi Autism Center will help autistic children increase their attention span.